2010
DOI: 10.1167/iovs.09-5041
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Retinal Ganglion Cell Layer Thickness in Patients with Type 1 Diabetes

Abstract: PURPOSE. To determine which retinal layers are most affected by diabetes and contribute to thinning of the inner retina and to investigate the relationship between retinal layer thickness (LT) and diabetes duration, diabetic retinopathy (DR) status, age, glycosylated hemoglobin (HbA1c), and the sex of the individual, in patients with type 1 diabetes who have no or minimal DR. METHODS. Mean LT was calculated for the individual retinal layers after automated segmentation of spectral domain-optical coherence tomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
251
5
9

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(282 citation statements)
references
References 32 publications
17
251
5
9
Order By: Relevance
“…This concentric analysis was designed for the present study to examine whether relative visual sensitivity changes are occurring with increasing distance from central fixation for the neuropathy group. Previously demonstrated diffuse loss of inner retinal integrity using OCT [11,12] supports this approach. A single average dB score is used to represent global, quadrant or concentric ring results.…”
Section: Methodsmentioning
confidence: 56%
See 1 more Smart Citation
“…This concentric analysis was designed for the present study to examine whether relative visual sensitivity changes are occurring with increasing distance from central fixation for the neuropathy group. Previously demonstrated diffuse loss of inner retinal integrity using OCT [11,12] supports this approach. A single average dB score is used to represent global, quadrant or concentric ring results.…”
Section: Methodsmentioning
confidence: 56%
“…Optical coherence tomography (OCT) has enabled high resolution, non-invasive imaging of the complex neural networks within the retina. Several OCT studies have suggested that diffuse neurodegenerative changes may precede the development of clinically visible vascular complications in the retinas of those with diabetes [8][9][10][11][12], and a link between thinning of the retinal nerve fibre layer and DPN has recently been demonstrated [13]. Evidence of retinal structural abnormality reinforces the prospect that visual function may be affected by neurodegenerative changes in diabetes-separate from the better-characterised visual dysfunction attributable to retinopathy [14].…”
Section: Introductionmentioning
confidence: 93%
“…For example, several studies showed a decreased retinal ganglion cell (RGC) layer thickness in patients with type 1 diabetes. 21 Moreover, in type 2 diabetic patients, neuroretinal alterations are supported both by a retinal function test, electroretinogram or microperimetry, 3,4 and neuroretinal histological evaluation. 22,23 To the best of our knowledge, only a few published studies exist testing GC-IPL and RNFL thicknesses in patients with no signs of DR using an imaging approach.…”
Section: P-valuementioning
confidence: 99%
“…Supporting its safety, the vector did not modify the retinal vascular bed and the ERG in non-diabetic rats. Finally, we explored the thinning of the retina which, owing to the neurodegeneration of the inner retina, occurs in diabetic humans, [42][43][44][45] and in some, [46][47][48][49] but not all, 50 diabetic rodent studies. We confirmed that retinal thinning does not occur at 6 weeks post-STZ-treatment, 47,49 and showed that the AAV2 vasoinhibin vector did not modify it.…”
Section: Aav2 Vectors Reverse Diabetic Retinal Alterations N Díaz-lezmentioning
confidence: 99%